The Poetic Reflection on Catherine Park from Pushkin to the Present Day: “The Obelisks of Glory and Victory” - Aida G. Razumovskaya (Два века русской классики)
The article comprehensively approaches the theme of military victories in the poetic reflection of Catherine Park in Tsarskoye Selo, enriching the perception of the semantics of the place that has the stable definition of the “motherland of muses” in the cultural memory. The extensive background of Russian poetry starting from the Enlightenment exposes the clear, obscure, or concealed evolution of the perception of the Park as the space of memory, historical reminiscences, and the pantheon of Russian glory. The analysis of the 18th–19th-centuries poetry material of various styles and trends, from classicism and romanticism to acmeism and its successors, makes transparent the choice of the objects for reflection as well as enables us to see the dynamics and transformation of their interpretation in various historical epochs. The author particularly focuses on the Park symbolism ascending to A. S. Pushkin’s poetry: Kagul obelisk and Chesme Column crowned with the victorious eagle. One can trace this Pushkin tradition of monuments’ interpretation in the artwork of those poets of Tsarskoye Selo who lived in the former Soviet Union or emigrated. The author concludes that poets’ appeal to the allegories of patriotism and dedicated service to the Motherland gained a prominent focus in crucial times, such as a war or revolution. In peaceful times, the landscape sceneries dominate in perception, transforming the artistic “Universe” of the Park into “the country of imagination” and the symbol of the Eden of love and creativity.